ROUND TABLE COOPERATIVE LEARNING TOWARDS STUDENTS' CONCEPT MASTERY AND SCIENCE ANXIETY IN LEARNING GLOBAL WARMING - Adinda Siwi Utami, - (2019)
Government choose cooperative learning as the strategy to gain concept mastery because of its student-centered activities. However, cooperative learning affect students' anxiety because they should have some interactions. There are so many types of cooperative learning, but Round Table is only used to learn language. So, this research investigated the effect of Round Table to students' concept mastery and science anxiety in learning global warming. In line with this objective, for the research, 48 7th grade students from one junior high school in Bandung were chosen into 2 groups, 24 students into experiment group with implementing Round Table and 26 students into control group with lecturing method. Pretest, post test, and science anxiety questionnaire were used as the data collection tools. The data analysis indicated that the students in the experiment groups showed greater gain of concept mastery than control group with N-Gain score from experiment group is 40.03 which categorized as medium improvement and control group is 18.2 which categorized as low improvement. But there is no significant difference between two group in science anxiety. Experiment group had an average rank of 25.56, while control had an average rank of 25.44. Therefore, Round Table is recommended to be used in learning global warming especially had a good implementation in grouping and writing stage to gain students' concept mastery, but there is needed continues research to decrease science anxiety.